Point Intercept Method for Estimating Biomass of Invasive Lantana (Lantana camara) in the Nilgiris, India - Najar, Muneer Ul Islam; Puyravaud, Jean-Philippe; Davidar, Priya (Indian Forester, 2019)
The aim of the present study was to develop a statistical model for biomass estimation of an invasive shrub Lantana camara, and to assess the role of tree canopy cover in determining its invasion density and above ground biomass. The study was carried out in patches of tropical montane evergreen ’shola’ forests that differed in disturbance regimes in the Nilgiris, South India. Point Intercept Method was calibrated to estimate the aboveground biomass of Lantana camara. A total of 15 plots (including four control plots), each of size 20 Ã— 20 m (0.04 ha) were studied. In each plot two line transects along two diagonals were laid down and a straight thin rod was dropped at an interval of 1 m. A total of 56 readings per plot were thus taken and the number of plant-rod contacts was noted down.The above ground biomass was estimated by harvest method for the calibration. The highest number of contacts and biomass values was found for the plots growing in open areas than under canopy cover. The model (2.359 + 0.018 (contacts) = log10 (biomass)) obtained was highly significant (p < 0.001, n = 9, R2 = 0.80). The observations show that the open canopy plots are refuges for L. camara and there is a significant change in its density in the plots studied under different degrees of forest canopy cover.